(3fXe eKdKGJ bWQHs - (3GdOejQj GdOjQjfj, YHO GdYRjR Hf CMeO Hf SYjO, J(B694(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdYXje GdHGQj (B*** (3NGdb GdCSeGY hGdCHUGQ , (B() (3JSdjej Ydi NjQ fHj (B*** (3CfXe ef eKdKGJ bWQHs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3hGdTjA EP jWQM jSei HGdbdG (B*** (3hGdHZV hGdJQc jSei HGdbdG , hLeY bdI (B() (3bdG (B*** (3hHGdbdjd LGA aj GdCTYGQs
(3fGbU GdBNQ, hjhLO HbjI GdfXe aj b(B80s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 13s
(3eYLe GdeDdajf(B: 2 / 157s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GddZIs